Penghindaran Pajak Cost of Debt dengan Kepemilikan Institusional Sebagai Variabel Moderasi - Dhananjaya, Kadek Krishna; Erawati, Ni Made Adi (E-Jurnal Akuntansi; Vol 33 No 7 (2023)DO - 10.24843/EJA.2023.v33.i07.p09, 2023)
This study aims to examine the effect of tax avoidance on the cost of debt and also examine the effect of institutional ownership in moderating the relationship between tax avoidance on the cost of debt in manufacturing companies listed on the Indonesia Stock Exchange. Quantitative research design in the form of associative. The number of observations was 93 companies using purposive sampling method. The researcher's analysis technique is multiple linear regression. The results of the study show that the tax avoidance variable has a positive effect on the cost of debt. Meanwhile, institutional ownership cannot moderate either strengthen or weaken the effect of tax avoidance on the cost of debt. Keywords: Tax avoidance, Cost of Debt, Institusional Ownership